COVID-19: risk accumulation among biologically and socially vulnerable older populations (2020)
Emerging data show that the health and economic impacts of COVID-19 are being disproportionately borne by individuals who are not only biologically, but also socially vulnerable. Based on preliminary data from Sweden and other reports, in this paper we propose a conceptual framework whereby different factors related to biological and social vulnerability may explain the specific COVID-19 burden among older people. There is already some evidence showing large social disparities in the prevention, treatment, prognosis and/or long-term consequences of COVID-19. The remaining question is to what extent these affect older adults specifically. We provide the rationale to address this question with scientific methods and proper study designs, where the interplay between individuals’ biomedical status and their social environment is the focus. Only through interdisciplinary research integrating biological, clinical and social data will we be able to provide new insights into the SARS-CoV-2 pandemic and inform actions aimed at reducing older adults’ vulnerability to COVID-19 or other similar pandemics in the future.